The Effect of Experiential Marketing Approach on Consumer Loyalty at Café Atsabe in Dili, Timor-Leste - Marques, Aíres Inácio; Karta, Ni Luh Putu Agustini (Language Assistance, 2025)
Experiential marketing is a marketing concept that aims to form loyal customers by touching their emotions and giving a positive feeling to products and services. Experiential marketing can be used as a tool to measure consumer satisfaction with a product or service. Customer engagement at this stage includes five things called Strategic Modules, which are modules that can be used to create various types of experiences for consumers, sense, feel, think, act and relate. The purpose of this reserach is to analyze the influence of sense, feel, think, act, and relate on the creation of consumer loyalty at Café Organiku Atsabe in Dili, Timor-Leste. The method used in this study is a quantitative method with loading factor analysis, inner model and hypothesis testing in PLS SEM with a bootstrapping procedure. The population in this study is consumers of Café Organiku Atsabe, the number of the population is 100 respondents. The results of the study can be concluded that five independent variables that were tested for their influence on consumer loyalty. The independent variable relates is the most influential variable with a path coefficient of 0.361, and the next variable is successively influential is the independent variable of sense with a path coefficient of 0.258 and the independent variable of act with a path coefficient of 0.323. Two other independent variables, namely feel and think, do not have the original value of the sample so they cannot be interpreted.